Protocol to the Convention on the Prohibition of Bacteriological (Biological) Weapons – History, Main Provisions, Significance and Reasons for Not Signing - S. V. Petrov; M. V. Supotnitskiy (Вестник войск РХБ защиты, 2021)
The Convention on the Prohibition of the Development, Production and Stockpiling of Bacteriological (Biological) and Toxin Weapons and on Their Destruction (BTWC) does not have a legally binding verification regime. An attempt by the Ad Hoc Group of Experts, created by the UN Committee on Disarmament, to strengthen the BTWC by developing a legally binding document – the Protocol, was blocked by the United States in July 2001. The purpose of this work is to study the history, main provisions, significance and reasons for not signing the Protocol to the BTWC. The attention is paid to the events in biological weapons control, which have led a number of countries to the understanding of the necessity to develop the Protocol. The background of the US actions to block this document is the subject of special consideration. During the Second Review Conference on the Implementation of the Convention (8–25 September 1986, Geneva) the USSR, the German Democratic Republic and the Hungarian People's Republic proposed to develop and adopt the Protocol as an addition to the BTWC. This document was supposed to establish general provisions, definitions of terms, lists of agents and toxins, lists of equipment that was present or used at production facilities, threshold quantities of biological agents designed to assess means and methods of protection. The proposed verification mechanism was based on three «pillars»: initial declarations with the basic information about the capabilities of each State Party; inspections to assess the reliability of the declarations; investigations to verify and confirm or not confirm the alleged non-compliance with the Convention. The verification regime was to be under the control of an international organization  – the Organization for the Prohibition of Bacteriological (Biological) and Toxin Weapons. However, the US military and pharmaceutical companies opposed the idea of international inspections. The then US Undersecretary of State for Arms Control and International Security, John Robert Bolton II, played a special role in blocking the Protocol. During the Fifth Review Conference in December 2001, he demanded the termination of the Ad Hoc Group of Experts mandate for negotiations under the pretext that any international agreement would constrain US actions. The current situation with biological weapons control should not be left to chance. Measures to strengthen the BTWC should be developed, taking into account the new fundamental changes in dual-use biotechnology. It should be borne in mind, that the Protocol, developed in the 1990s, is outdated nowadays.